Stylohyoid Syndrome and its Surgical Treatment - A Case Report and Review of the Literature - Islam Abdou Elzahaby; Elsherbini Elazazy Elshal (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2017)
Stylohyoid syndrome or eagle's syndrome is caused by calcification of the stylohyoid ligament or elongation of the bony styloid process. It may remain asymptomatic or it may present with facial neuralgia, foreign body sensation in pharynx, throat pain or even otalgia and cephalgia. Diagnosis is mainly based on clinical examination and confirmed by the radiological findings. The mainstay treatment is surgical excision via external approach or intraoral approach. We are reporting a case of unilateral stylohyoid syndrome along with the literature review.